Estudo clínico randomizado do uso da sonda enteral pós – pilórica versus gástrica em pacientes hospitalizados - Opsfelder, Leandro Augusto Kuhl (2019)
This randomized clinical study has objective to measure the nutritional response in patients using enteral probe in the post-pyloric position and in patients who received an enteral diet in the gastric position. Methods: Thirty-five patients hospitalized with exclusive enteral therapy were randomly divided into two groups, the only difference being the positioning of the probe: 18 patients with enteral probe in the post-pyloric position and 17 patients in the position for a defined period of 28 days. We used the serum values of albumin and transferrin as biochemical variables. As anthropometric variables, we measured the percentage of body fat and the body mass index provided by tetra-polar electric bioimpedance. The complications were represented by the variables diarrhea, vomiting and interruptions of the diet. Results: with regard to dietary indicators, it was possible to observe that the prescribed diet, the diet administered and the number of interruptions of the diet presented a statistically significant variation during the follow-up period. Both experimental groups increased the amount of calories prescribed and administered in the diet and reduced the number of interruptions of the diet, but with no difference between them. There was also an increase in the number of diarrhea records, with the main effect of time (p = 0.011), that is, also with no difference between the experimental groups (p [interaction] = 0.748). Regarding the indicators of body composition and blood parameters during the 28 days of follow-up in both experimental groups. While the patients' BMI decreased over time (no differences between groups), no statistically significant changes were observed in body fat indexes during follow-up. Among blood parameters, transferrin levels (p = 0.003) increased over time in a similar way between the post-pyloric and gastric groups. However, group vs time interaction was observed with respect to albumin (p = 0.002). Although similar values were observed up to day 21, the post-pyloric group presented increase in albumin levels compared to the gastric group at day 28. Conclusion: The albumin variable presented a statistically significant increase in the post-pyloric group in relation to the gastric group in the last week of the study and the transferrin variable was statistically significant in relation to the study time, but without significance between the groups.